2015
DOI: 10.4081/ijfs.2015.5383
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two loop-mediated isothermal amplification methods for the detection of Salmonella Enteritidis and Listeria monocytogenes in artificially contaminated ready-to eat fresh products

Abstract: In the present study, the effectiveness of two loop-mediated isothermal amplification (LAMP) assays was evaluated. Samples of romaine lettuce, strawberries, cherry tomatoes, green onions and sour berries were inoculated with known dilutions (100-108 CFU/g of produce) of S. Enteritidis and L. monocytogenes. With LAMP, assay pathogens can be detected in less than 60 min. The limits of detection of S. Enteritidis and L. monocytogenes depended on the food sample tested and on the presence of enrichment step. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Cherry tomato is a major garden product popular among consumers that is low in calories and rich in lycopene, vitamin C, and β‐carotene (Soto‐Zamora and others ; Rosales and others ; Yun and others ). It is usually sold ready to eat, and often consumed raw or in salads (Birmpa and others ). However, being a climacteric fruit, cherry tomato ripens, and senesces rapidly after harvest owing to transpiration and respiration, and is easily damaged and contaminated by microorganisms (Fagundes and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Cherry tomato is a major garden product popular among consumers that is low in calories and rich in lycopene, vitamin C, and β‐carotene (Soto‐Zamora and others ; Rosales and others ; Yun and others ). It is usually sold ready to eat, and often consumed raw or in salads (Birmpa and others ). However, being a climacteric fruit, cherry tomato ripens, and senesces rapidly after harvest owing to transpiration and respiration, and is easily damaged and contaminated by microorganisms (Fagundes and others ).…”
Section: Introductionmentioning
confidence: 99%
“…There were 3 (for IS6110) and 1 (for IS1081) RPA‐S reactions that exhibited an indefinite orange‐green color after adding SYBR Green I, which were interpreted as negative for Mtb detection. A previous study showed that there was no significant difference between the LAMP results detected by agarose gel electrophoresis or naked eye detection of LAMP products after SYBR Green I addition . Although SYBR Green I exhibits good sensitivity for DNA detection, false negatives somehow occur when the DNA content is low .…”
Section: Discussionmentioning
confidence: 98%
“…It is a novel isothermal amplification method and is used in rapid diagnostic testing of viruses [1], bacteria [2], fungi [3], and parasites [4] in all sorts of biological samples. Derived from the famous classical polymerase chain reaction (PCR), it presents many advantages like to be low-cost, no thermocycler required, tolerant to sample matrix inhibitors And it performs with the various products detection methods like fluorescent dye, real-time detection, lateral flow assays, and gel analysis [ Fig.…”
Section: Introductionmentioning
confidence: 99%